Blow-Up in a Slow Diffusive -Laplace Equation with the Neumann Boundary Conditions - Chengyuan Qu; Bo Liang (Abstract and Applied Analysis)
We study a slow diffusive -Laplace equation in a bounded domain with the Neumann boundary conditions. A natural energy is associated to the equation. It is shown that the solution blows up in finite time with the nonpositive initial energy, based on an energy technique. Furthermore, under some assumptions of initial data, we prove that the solutions with bounded initial energy also blow up.